Hydrometeorological controls on net carbon dioxide exchange over a temperate desert steppe in Inner Mongolia, China - Song, Jiaxin; Zhou, Li; Zhou, Guangsheng; Wang, Yu; Zhang, Sen; Yan, Yujie (Frontiers in Ecology and Evolution, 2023)
Understanding the effect of environmental factors on the net ecosystem CO2 exchange (NEE) and the response of NEE to rainfall events is of great significance for an accurate understanding of the carbon cycle for desert steppe ecosystems. Based on the long-term (2011-2018) eddy covariance flux data of a temperate desert steppe in Inner Mongolia, China, this study used path analysis to analyze the combined impact of the environmental factors on NEE. The results showed that during the growing season, vapor pressure deficit (VPD) and soil water content (SWC) was the most prominent environmental factor for the daytime NEE and nighttime NEE, respectively. NEE responds differently to individual environmental factors among multi-year climatic conditions. The size of rainfall event has significant impacts on NEE, it can effectively promote the CO2 uptake of the desert steppe ecosystem when rainfall event size is greater than 5 mm, and the NEE response increased with the rainfall event size. Moreover, NEE peaked approximately 1-3 days after a 5-10 mm rainfall event, while the rainfall event size > 10 mm, it would take 3-5 days for NEE to reach a peak value; and yet, small rainfall events (< 5 mm) slightly increased CO2 emissions. During the growing season, carbon uptake increased with monthly rainfall, except in May. Our results are important for understanding the carbon cycle and its control mechanisms in the temperate desert steppe of Inner Mongolia.